2016
DOI: 10.1371/journal.pone.0153705
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Regulatory CD4+ T Cells That Share Identical TCRs Are Derived from Common Clones

Abstract: Results from studies comparing the diversity and specificity of the TCR repertoires expressed by conventional (Tconv) and regulatory (Treg) CD4+ T cell have varied depending on the experimental system employed. We developed a new model in which T cells express a single fixed TCRα chain, randomly rearranged endogenous TCRβ chains, and a Foxp3-GFP reporter. We purified CD4+Foxp3- and CD4+Foxp3+ cells, then performed biased controlled multiplex PCR and high throughput sequencing of endogenous TCRβ chains. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Knowing that CD4 + T cells were required for control of ZIKV infection and that we could detect a strong antigen specific CD4 + T cell response in the mice, we hypothesized that the TCR repertoire specific for the different CD4 epitopes would contain a high degree of diversity. Using techniques we have previously established to identify TCRβ sequences diversity of CD4 + T cells [ 65 ], we noted a striking degree of diversity in the TCRβ sequences for an individual ZIKV-specific epitope within a mouse and between mice ( Fig 5 ). We were unable to detect shared “public” TCRs for any epitope between mice confirming our hypothesis that the ZIKV epitope specific T cell responses were clonally diverse suggesting a broadly reactive T cell pool.…”
Section: Discussionmentioning
confidence: 95%
“…Knowing that CD4 + T cells were required for control of ZIKV infection and that we could detect a strong antigen specific CD4 + T cell response in the mice, we hypothesized that the TCR repertoire specific for the different CD4 epitopes would contain a high degree of diversity. Using techniques we have previously established to identify TCRβ sequences diversity of CD4 + T cells [ 65 ], we noted a striking degree of diversity in the TCRβ sequences for an individual ZIKV-specific epitope within a mouse and between mice ( Fig 5 ). We were unable to detect shared “public” TCRs for any epitope between mice confirming our hypothesis that the ZIKV epitope specific T cell responses were clonally diverse suggesting a broadly reactive T cell pool.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that 12% of T-cell receptors were shared by Tregs and conventional effector T cells at the DNA level suggesting a common progenitor cell [31]. Tregs also tend to express markers of the effectors that they target.…”
Section: Discussionmentioning
confidence: 99%
“…Since SPIRAL mandates antigen-specific inhibition of ineffective T cell responses by Tregs (Usharauli and Kamala, 2018;Pohar et al, 2018;Akkaya et al, 2019), their sensing of IL-2 as a proxy for such ineffective T cell responses must be antigen-specific as well (Setoguchi et al, 2005;Almeida et al, 2006;Amado et al, 2013;Liu et al, 2015). In other words, Tregs cannot just sense IL-2 produced by random T cells but instead must share antigen-specificity in the form of crossreactivity with such IL-2 producing T cells (Wolf et al, 2016). Applying this principle to the thymus suggests that IL-2p T cell and Treg precursors whose progeny recognize similar epitopes in the periphery via shared epitope cross-reactivity must be able to do likewise in the thymus as well.…”
Section: Dyads Of Treg and Il-2p T Cell Precursors Allow Their Escapementioning
confidence: 99%